Molecular biomarkers to help select neoadjuvant systemic therapy for urothelial carcinoma of the bladder - Laukhtina, Ekaterina; Pradere, Benjamin; Lemberger, Ursula; Karakiewicz, Pierre I; Fajkovic, Harun; Shariat, Shahrokh F (Current opinion in urology, 2022)
PURPOSE OF REVIEW: In this review, we aimed to summarize the available evidence on pretreatment molecular biomarkers that may help to predict oncologic and pathologic outcomes in patients treated with neoadjuvant systemic therapy (NAST) for urothelial carcinoma of the bladder (UCB). RECENT FINDINGS: Several readily available and easily measurable blood-based biomarkers (e.g., neutrophil to lymphocyte or platelet-lymphocyte ratios) seems to help improve the selection of UCB patients who are most likely to benefit from NAST. Recent evidence suggests liquid biopsy including circulating tumor DNA (ctDNA) to be a promising tool to guide the administration of NAST in UCB patients. Pretreatment molecular and genetic characterization of transurethral resection of the bladder tumor samples may also help understand the tumor biology as luminal and basal tumor subtypes seems to be more responsive to NAST, while claudin-low and luminal-infiltrated tumor subtypes are less. In the context of neoadjuvant immunotherapy, programmed death-ligand 1 (PD-L1) status and ctDNA remain the only biomarker with possible value as the clinical utility of tumor mutational burden remains controversial/poor. SUMMARY: Biomarker approach is a necessary step to usher the age of precision/personalized medicine for muscle-invasive UCB with the overarching good to prevent both over- and under-therapy. The present review may offer a robust framework to compare and assess current and future molecular biomarkers for the selection of NAST in muscle-invasive UCB.
Keywords: Biomarkers, Tumor; Circulating Tumor DNA; Neoadjuvant Therapy; cirkulující nádorová DNA; nádorové biomarkery; neoadjuvantní terapie; močový měchýř; Humans; lidé; nádory močového měchýře; Urinary Bladder Neoplasms; Urinary Bladder; Carcinoma, Transitional Cell; karcinom z přechodných buněk